European Social Survey: 10 Years in Lithuania - Žvaliauskas, Giedrius (Sociologija. Mintis ir veiksmas, 2018)
A short review of the European Social Survey (ESS) and its 8th wave module on welfare attitudes. The review presents a detailed description of the variables used in the ESS questionnaire in a 2017 survey conducted in Lithuania and links to its results.
Keywords: none